Literacy Culture Behind Yogyakarta's Success in the 2026 Academic Competency Test - Eki Yulia Susanti; Agustina Tri Wijayanti; Sudrajat Sudrajat; Finan Ahsani Taqwim (Assyfa Journal of Islamic Studies, 2026)
The Special Region of Yogyakarta achieved the highest national performance in the 2026 Academic Competency Test, highlighting the need to examine educational factors associated with students’ academic achievement, including literacy culture. This study synthesizes the relationship between literacy culture and academic achievement and examines its implications for interpreting Yogyakarta’s test results. A systematic literature review was conducted using a selection process guided by PRISMA 2020. The corpus comprised 21 publications issued between 2020 and 2026, including journal articles, conference proceedings, a thesis, a preprint, and official national and international reports. The publications were retrieved from Google Scholar, Scopus, ERIC, Crossref, Dimensions, and Garuda and analyzed through thematic content analysis. The synthesis indicates that literacy culture is associated with reading habits, information comprehension and literacy, critical thinking, problem-solving skills, and various indicators of academic achievement. These relationships are also shaped by family support, teacher competence, the school environment, learning motivation, and socioeconomic conditions. The findings position literacy culture as a strategic component of the educational ecosystem that may support academic achievement. In the context of Yogyakarta’s 2026 Academic Competency Test results, literacy culture provides a relevant conceptual perspective for interpreting the province’s performance; however, it cannot be regarded as a direct causal factor without further empirical investigation.